Strategi Promosi Wisata Kota Bukittinggi Melalui Kuliner Nasi Kapau - Pepy Afrilian; Harry Yulianda; Atika Afriani (Indonesian Journal of Tourism and Leisure, 2021)
Culinary has become its attraction that captivates the hearts of tourists. This is realized by the Bukittinggi City Government which will develop its tourist attraction through the culinary tourism potential of Nasi Kapau. Culinary Tourism started from additional facilities in the distribution of tourist activities but now the position of Nasi Kapau has turned into a tourist attraction that can be side by side with other attractions. To find out the position of Nasi Kapau to be used as a tourist promotion tool of Bukittinggi City, it needs to be started with an analysis of strengths, opportunities, weaknesses, and threats internally and externally, research seeks information by interviews by all Nasi swords that sell in bukittinggi slope market and spread angket to tourists who eat Nasi Kapau in bukittinggi slope market. The data obtained is analyzed descriptively about the marketing mix and the next data from the questionnaire is given weight and entered in the SWOT matrix so that it can answer the appropriate strategy for the promotion of Bukittinggi City through Nasi Kapau culinary tour. The results obtained are strategies that are suitable for the promotion of the city of Bukittinggi through Nasi Kapau Culinary tour is an aggressive strategy. Continuous promotion can also be done by mouth-to-mouth method or make Nasi Kapau as a talking point so as to attract other tourists to visit Bukittinggi out of curiosity about the taste of Nasi Kapau. In addition, Nasi Kapau costomers has been classified as a royal costomers so that it can dream up its review with pleasure.